Analisis Tingkat Pemahaman Akuntansi Mahasiswa Berdasarkan Hasil Belajar Matematika Ekonomi - Faizah Adisty; Indah Pertiwi (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2020)
This research aims to determine the correlation between mathematics economics courses and an introduction to accounting. The reason for choosing the title is because there are many economic principles that use mathematics. Accounting has a close relationship with mathematics. Many students who master mathematics are considered able to solve accounting cases well too. The concept of the dual aspect, which is the basic concept of accounting, is expressed as a mathematical equation, called an accounting equation. Accounting calculations such as the calculation of depreciation, determination of loan installments, determination of cash prices in the case of the purchase of a lease and installment system require the use of mathematical techniques. All of this requires mathematical knowledge where the mastery of basic mathematical concepts is important for accounting students to master well in the Introduction to Accounting course. The samples of this research are students enrolled in the 2018/2019 school year. The results of this research, calculation of the correlation coefficient (r) = 4. Based on statistical calculations, it can be concluded that the mathematics economics course has a positive effect on the introductory accounting courses to D3 Accounting students at the University of Pamulang.